Wheat Flour Substitution with Retrograded Banana Flour to Produce Cookies Possessing Good Physical Characteristics and Low Glycemic Index - Cahyana, Yana; Restiani, Resti (KnE Life Sciences, 2017)
Diabetes Mellitus is one of degenerative diseases (DM) affecting many people around the world. It is thus important to prevent DM by choosing the right food with low in glycemic index (GI). Modified banana flour-based low GI cookies could be the solution in which the modification may be carried out by retrograding the flour. The purpose of this study was to determine the right proportion between retrogradated banana flour and wheat flour to produce cookies with low glycemic index and good characteristics. The method was randomized block design with six treatments and three time replications. The treatments were ratio (in percentage) of modified (retrogradated) banana flour with wheat flour 0:100, 50:50, 60:40, 70:30, 80:20, and 90:10. The result showed that cookies made of 90 % retrogradated banana flour and 10 % wheat flour was the best treatment with GI value of 57,20. Physical analysis comprised of hardness and lightness (L*) were around 1593.44 gF and 57,22, respectively. Keyword: wheat flour, glycemic index, cookies, retrogradated banana flour